2021
DOI: 10.1093/cz/zoab025
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance cue communication is shaped by emitter diet and receiver background risk in Trinidadian guppies

Abstract: In animal communication systems, individuals that detect a cue (i.e., ‘receivers’) are often influenced by characteristics of the cue emitter. For instance, in many species, receivers avoid chemical cues that are released by emitters experiencing disturbance. These chemical ‘disturbance cues’ appear to benefit receivers by warning them about nearby danger, such as a predator’s approach. While the active ingredients in disturbance cues have been largely unexplored, by-products of metabolized protein are thought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…However, in a latter study, reagent-grade urea [CO(NH 2 ) 2 ] was found to elicit avoidance responses in both species, and at an intensity matching their responses to conspecific disturbance cues (Brown et al 2012). More recently, Goldman et al (2021) found support for the hypothesis that the disturbance cues of guppies are affected by diet. Receivers responded more intensely to disturbance cues from donors that were fed a protein-rich diet and an overall larger diet.…”
Section: Fishesmentioning
confidence: 84%
See 1 more Smart Citation
“…However, in a latter study, reagent-grade urea [CO(NH 2 ) 2 ] was found to elicit avoidance responses in both species, and at an intensity matching their responses to conspecific disturbance cues (Brown et al 2012). More recently, Goldman et al (2021) found support for the hypothesis that the disturbance cues of guppies are affected by diet. Receivers responded more intensely to disturbance cues from donors that were fed a protein-rich diet and an overall larger diet.…”
Section: Fishesmentioning
confidence: 84%
“…Brown et al (2010) observed responses to alarm cues in Trinidadian guppies that differed based on the donor population, suggesting that local diet specializations might drive populationspecificity in alarm cue production. Similarly, Goldman et al (2021) found that that diet quality and quantity influence disturbance cue production in guppies, which could similarly shape responses to conspecific vs. heterospecific disturbance cues.…”
Section: Species Specificitymentioning
confidence: 87%
“…While some previous studies of discrimination under different levels of background predation found greater discrimination at higher risk levels, these studies used stimuli that were related to predators of the respective study species (Burger & Gochfeld, 1990; Goldman et al, 2021). In the Burger and Gochfeld (1990) study, walking humans were the experimental treatment for black iguanas in a region where they were hunted by humans.…”
Section: Discussionmentioning
confidence: 99%
“…In the Burger and Gochfeld (1990) study, walking humans were the experimental treatment for black iguanas in a region where they were hunted by humans. In the Goldman et al (2021) study, guppies discriminated between alarm cues from conspecifics that warned of nearby danger. Similarly, polymorphic frogs ( Discoglossus galganoi ) were approached by plastic snake models to quantify FID (Zamora‐Camacho & Aragón, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation